Study of morphology and gas separation properties of polysulfone/titanium dioxide mixed matrix membranes - Moradihamedani, Pourya; Ibrahim, Nor Azowa; Wan Yunus, Wan Md Zin; Yusof, Nor Azah (Wiley, 2015)
Polysulfone (PSf)-based mixed matrix membranes (MMMs) with the incorporation of titanium dioxide (TiO2) nanoparticles were prepared. Distribution and agglomeration of TiO2 in polymer matrix and also surface of membranes were observed by scanning electron microscopy, transmission electron microscopy, and energy dispersive X-ray. Variation in surface roughness of MMMs with different TiO2 loadings was analyzed by atomic force microscopy. Physical properties of membranes before and after cross-linking were identified through thermal gravimetric analysis. At low TiO2 loadings (≤3 wt%), both CO2 and CH4 permeabilities decreased and consequently gas selectivity improved and reached to 36.5 at 3 bar pressure. Interestingly, PSf/TiO2 3 wt% membrane did not allow to CH4 molecules to pass through the membrane and this sample just had CO2 permeability at 1 bar pressure. Gas permeability increased considerably at high filler contents (≥5 wt%) and CO2 permeance reached to 37.7 GPU for PSf/TiO2 7 wt% at 7 bar pressure. It was detected that, critical nanoparticle aggregation has occurred at higher filler loadings (≥5 wt%), which contributed to formation of macrovoids and defects in MMMs. Accordingly, MMMs with higher gas permeance and lower gas selectivity were prepared in higher TiO2 contents (≥5 wt%).